Social Performance in Hospitals: A systematic Review of Social Measurement Properties of Hospital Accreditation Committee (KARS) Instruments - Layman, Chrisanty V.; Sasmoko; Budiastuti, Dyah; Sanny, Lim (International Journal of Psychosocial Rehabilitation, 2020)
Recent aspirations for social centered health care services have been reaffirmed in the wake of Indonesia’s participation in the universal healthcare coverage scheme (UHC). As the main provider of health services in the country, it is imperative for hospital to measure its social performance. However, attempts to assess social performance has been challenging, given the different perceptionover the term ‘social performance’. The result has been a proliferation of instruments, measured separately by individual hospitals. A reference point from the current accreditation standard measurements for hospitals in Indonesia has been monitored by an independent non-profit organization,Hospital Accreditation Committee (KomiteAkreditasiRumahSakit or KARS) recognized by The International Society for Quality in Health Care (ISQua). This study will evaluate the standards in KARS instrument managed and analyzed using QSR NVIVOallowing relevant instruments to be identified and summarized. This result of the study is a synthesis on the properties and categories of instruments that would indicate a measure for social performance. This will provide appropriate selection of current instruments proposed to capture hospital social performance in Indonesia.